Francis E. Walter Dam, Lehigh River Basin, Lehigh River, Pennsylvania. Condition Report. Dam, Outlet Works and Spillway. - ARMY ENGINEER DISTRICT PHILADELPHIA PA (1977)
The third periodic inspection of Francis E. Walter Dam was held on 10 Nov. 1976 by representatives of the North Atlantic Division and the Philadelphia District Corps of Engineers. The service bridge, intake tower, outlet slab, discharge channel, embankment, spillway and upstream reservoir area of this dam were inspected by direct visual observation and instrumentation analysis. The overall condition of the project is considered good. Some slope irregularities were observed and additional use of inclinometers was requested to monitor the upstream and downstream slopes. Minor remedial repair work can be accomplished by routine maintenance. (Author)